The allograft injury marker CXCL9 determines prognosis of anti‐HLA antibodies after lung transplantation. Issue 2 (12th November 2021) - Shino, Michael Y.; Zhang, Qiuheng; Li, Ning; Derhovanessian, Ariss; Ramsey, Allison; Saggar, Rajan; Britton, Ian N.; Amubieya, Olawale O.; Lari, Shahrzad M.; Hickey, Michelle; Reed, Elaine F.; Noble, Paul W.; et al.
Abstract : Despite the common detection of non‐donor specific anti‐HLA antibodies (non‐DSAs) after lung transplantation, their clinical significance remains unclear. In this retrospective single‐center cohort study of 325 lung transplant recipients, we evaluated the association between donor‐specific HLA antibodies (DSAs) and non‐DSAs with subsequent CLAD development. DSAs were detected in 30% of recipients and were associated with increased CLAD risk, with higher HRs for both de novo and high MFI (>5000) DSAs. Non‐DSAs were detected in 56% of recipients, and 85% of DSA positive tests had concurrent non‐DSAs. In general, non‐DSAs did not increase CLAD risk in multivariable models accounting for DSAs. However, non‐DSAs in conjunction with high BAL CXCL9 levels were associated with increased CLAD risk. Multivariable proportional hazards models demonstrate the importance of the HLA antibody‐CXCL9 interaction: CLAD risk increases when HLA antibodies (both DSAs and non‐DSAs) are detected in conjunction with high CXCL9. Conversely, CLAD risk is not increased when HLA antibodies are detected with low CXCL9. This study supports the potential utility of BAL CXCL9 measurement as a biomarker to risk stratify HLA antibodies for future CLAD. The ability to discriminate between high versus low‐risk HLA antibodies may improve management by allowing for guided treatment decisions. Abstract : This study evaluates donor‐specific and non‐donor‐specific HLA antibody development after lung transplantation and finds a strong interaction between HLA antibodies, bronchoalveolar lavage fluid CXCL9 levels and subsequent risk of chronic lung allograft dysfunction.